Aplicación de la geomática en el análisis geomorfológico de la subcuenca de la quebrada Cojup ( Huaraz, Ancash) - Meléndez de la Cruz, Juan Felipe (2005)
This investigation is framed in the applied geography field by the use of geomorphology analysis, satellital images and geomatic techniques. Main endogenous and exogenous causes that produce removal process in mass in the sub-river basin of the stream Cojup, that is concordant in its low part with the city of Huaraz, are identified. Main process of present occupation of this city supported with «Model of Elevation of Relieve (DEM) and coincident with of very high dangerous zones, and consequently incompatible with welcome capacity is identified.